2020
DOI: 10.3389/fped.2020.612467
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Maintaining the Hemostatic Balance in Children Undergoing Extracorporeal Membrane Oxygenation: A Systematic Literature Review

Abstract: Background: Despite advances in technology and clinical experience, the incidence of hemostatic complications, including bleeding and thrombosis, remains high in children supported with extracorporeal membrane oxygenation (ECMO). These hemostatic complications are important to prevent, since they are associated with increased morbidity and mortality. This systematic literature review aims to outline the most important risk factors for hemostatic complications in children undergoing ECMO treatment, to summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
1
18
0
6
Order By: Relevance
“…However, the sample (58 patients) they included was too small, and most studies were case reports that could not compare the efficacy of bivalirudin and heparin. Drop JGF et al [8] conducted a systematic review to summarize the reported alternative anticoagulant drugs used in pediatric ECMO, and three studies described bivalirudin. Pharmacokinetic data, precise dosing, and monitoring guidelines are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, the sample (58 patients) they included was too small, and most studies were case reports that could not compare the efficacy of bivalirudin and heparin. Drop JGF et al [8] conducted a systematic review to summarize the reported alternative anticoagulant drugs used in pediatric ECMO, and three studies described bivalirudin. Pharmacokinetic data, precise dosing, and monitoring guidelines are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors influence the risk for hemostatic complications, such as ECMO indications, ECMO circuitry, infections, surgery, underlying diseases, ECMO duration, and anticoagulation and transfusion management. 5 This review shows that the existing pediatric ECMO literature describing hemostatic tests and/or hemostatic outcomes does not clearly describe many essential factors that influence the hemostatic balance and, consequently, patient outcomes. To assess the contribution of individual components on outcome and to define best practice, it is important to be able to compare practices and results internationally.…”
Section: Discussionmentioning
confidence: 97%
“…Broman et al have made a first step toward a standardized approach to defining cannula practices in ECMO patients 15 . Pump type, mode, and location of cannulation have been associated with bleeding and thrombotic complications in several studies and are important to describe 5 . Given the increase in available technology for ECMO support, specific description of circuitry is essential to identify potential variances in technology performance and affect factors such as hemolysis and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations